Multisensor Based Neutral Function Identification of Solenoid Valve - Yanqing Guo; Yongling Fu; Xiaoye Qi; Chun Cao (International Journal of Distributed Sensor Networks)
Condition monitoring of hydraulic systems has been using automatic control in industrial system. In this paper, a sensor network based intelligent control is proposed for efficient solenoid valve identification. The detection system learns to detect the change of output pressure of multipoints that represent a more complicated task. Linear correlation analysis is introduced for feature extraction, which allows for a significant reduction in the dimension of original data without compromising the change detection performance. Implemented as an agent identifying the valve types under measurement, the support vector machine classifier achieves a significant high accuracy in identification and an increase in deployment efficiency. Experimental results prove that the system is feasible for application designs and could be implemented on technological platforms.